EPISTLE FROM “DAYS OF SLAVERY” (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article will consider the nature of the epistolary form in the story of S. Karachev “In the days without freedom” one of the founders of Kyrgyz literature. Those. the purpose, tasks, specifics and features of the use of the epistolary form used in the specified work areanalyzed.
Keywords: Epistolary form, epistolary genre, writing, specifics of writing, nature of love letters.